Impact of molar teeth distalization with clear aligners on occlusal vertical dimension: a retrospective study - Silvia Caruso; Alessandro Nota; Shideh Ehsani; Elena Maddalone; Kenji Ojima; Simona Tecco (BMC, 2019)
Abstract Background A common strategy in the non-extraction treatment of Class II molar relationship is maxillary molar distalization, which could increase lower face height and cause clockwise mandibular rotation. The aim of this retrospective study was to analyse the effects on vertical dentoskeletal dimension of young adults treated with sequential distalization with orthodontic aligners. Methods Lateral cephalometric radiographs of 10 subjects (8 females 2 males; mean age 22.7 ± 5.3 years) treated with upper molars sequential distalization with orthodontic aligners (Invisalign, Align Technology, San Josè, California, USA) were analyzed. Results No statistically significant difference was observed for the primary outcome SN-GoGn between T0 and T1 and it was recorded a mean variation of 0.1 ± 2.0 degrees. Statistically significant differences were found in the linear position of the upper molars (6-PP, 7-PP) the molar class relationship parameter (MR) and the upper incisive inclination (1^PP) with at least p < 0.01. Conclusions Upper molar distalization with orthodontic aligners guarantee an excellent control of the vertical dimension representing an ideal solution for the treatment of hyperdivergent or openbite subjects. It also allows an excellent control of the incisal torque without loss of anchorage during the orthodontic procedure.